Long‐term outcomes of hemi‐automated lamellar keratoplasty. (27th June 2018) - Fuest, Matthias; Liu, Yu‐Chi; Arundhati, Anshu; Li, Lim; Tan, Donald; Mehta, Jodhbir S
Abstract: Importance: To describe long‐term outcomes of hemi‐automated lamellar keratoplasty (HALK). Background: HALK is a hybrid anterior lamellar keratoplasty technique for corneas with anterior to mid‐stromal scars and topographical irregularities. Design: Prospective interventional case series. Participants: Thirty‐five eyes of 35 consecutive patients undergoing HALK at a single tertiary referral centre from 2007 to 2016. Methods: Patients were followed up for a mean period of 61.4 ± 29.2 months. Main Outcome Measure: Uncorrected visual acuity (UCVA), best spectacle‐corrected visual acuity (BSCVA), spherical equivalent (SE) and cylinder, endothelial cell density (ECD), central corneal thickness (CCT), graft survival and complications were analysed. Results: The most common indications for HALK were scars because of contact lens associated infectious keratitis (29%), unknown origin (26%) or corneal dystrophies (14%). Five patients had a previous keratoplasty ( n = 4; deep anterior lamellar keratoplasty, n = 1). Two HALKs failed at 22 and 32 months follow‐up. No graft rejections occurred. UCVA improved from 0.91 ± 0.31 to 0.58 ± 0.35 and BSCVA from 0.66 ± 0.30 to 0.21 ± 0.20 logMAR ( P < 0.001) at the last follow‐up. Astigmatism ( P = 0.2), SE ( P = 0.8) and ECD ( P = 0.4) did not change significantly during follow‐up. CCT increased from 490 to 560 μm ( P = 0.004). Kaplan–Meier estimated survival for all HALK cases was 90.6 (95% confidence interval 82.6–98.5) months with a survival probability of 96% at 12 months and 92% at 3, 5 and 7 years of follow‐up. Conclusions and Relevance: HALK provides excellent graft survival in primary cases and in patients with prior keratoplasty as well as significant improvement in visual acuity with low complication rates.